The effectiveness of green product positioning and marketing strategies towards purchase intention in Malaysia - amin, M.; Uthamaputhran, S.; Ali, F. (Inderscience Enterprise, 2015)
This study aims to investigate the effect of green positioning strategies towards product attitudes and customer's intentions to purchase. Data was collected from 500 customers of Giant and Econ save supermarket by distributing the questionnaires. Results of this study show that emotional benefits and functional attributes have significant relationship with product attributes and product attributes has significant relationship with purchase intentions. Findings from this study suggested that functional attributes and emotional benefits have become an important aspect in green product positioning to convince the customers to buy the green products